Multiple Myeloma: Impact on the Skeletal System - a Review of the Literature - Stupecka, Aleksandra; Ciechomski, Kamil; Cecuła, Wiktoria; Rypel-Bośka, Joanna; Siuta , Natalia; Migiel, Marcin; Brynczka, Izabela; Goleniewska, Klaudia; Miaśnikiewicz, Jakub (Quality in Sport, 2025)
Background. Multiple myeloma is a cancerous disease of the hematopoietic system marked by the uncontrolled proliferation of monoclonal plasma cells within the bone marrow. Bone disease is a characteristic feature and a diagnostic criterion of multiple myeloma. Aim. This paper aims to discuss the pathophysiological mechanisms underlying bone damage in multiple myeloma and to present current diagnostic and therapeutic approaches designed to improve clinical outcomes in patients affected by myeloma bone disease. Material and methods. A review of the scientific literature from the past eight years was conducted using topic-specific keywords, primarily through databases such as PubMed and Google Scholar. Results. Bone mass loss is a complex process that involves elevated osteoclast activity, impaired osteoblast function, and the release of pro-inflammatory cytokines, resulting in a disruption of the balance between bone resorption and formation. As a consequence, patients may develop chronic bone pain, pathological fractures, and postural changes. Therapeutic strategies that aim to slow the course of the disease and inhibit osteoclast activity are essential for minimizing the risk of skeletal-related complications and markedly enhancing patients' quality of life. Conclusion. Multiple myeloma is a malignancy that frequently leads to bone damage. This review discusses the underlying mechanisms, diagnostic methods, and current treatments aimed at preventing skeletal complications and improving patient outcomes